System Modelling and Database for Doctor Reservation Application Based on Location - Arif, Achmad Yusron; Neno, Friden Elefri; Henderi, Henderi (SENATIK STT Adisutjipto, 2018)
There are many benefits of using information technology in the health sector such as to make hospital information system, clinic or puskesmas. Now, queuing reservation system is still done manually or just using SMS / by phone, required a system that can be used patient to find and do doctor reservation. Thus, the patient when it comes can be directly checked without having to wait for a long time. Another problem when someone goes to a new area, then need medical services as soon as possible because of that is needed an application which contains information of doctor / clinic nearby. Therefore, in this paper will be discussed draft doctor reservation application by displaying a list of doctors. So the patient simply open the application and will be displayed a list of doctors, this will certainly facilitate the patient in finding and make a doctor reservation.